Eksplorasi resiliensi ekonomi perspektif islam: Tinjauan literatur terpilih - Muhammad Arfan Harahap; Julfan Saputra (Nur Science Institute, 2026)
This study introduces and develops Islamic perspective economic resilience as a new concept specific to the discipline of Islamic economics through a review of selected literature. Through a Systematic Literature Review (SLR) guided by the PRISMA protocol, 62 selected articles published between 2020 and 2026 were analyzed from the Scopus and dan google scholar database. This analysis synthesizes insights from the selected literature to identify the meaning of the Islamic perspective on economic resilience and to develop the concept. The concept of Islamic perspective economic resilience positions the mechanism of spirituality as the main foundation for constructing economic resilience by incorporating patience and istirja' as instruments. By integrating economic and spiritual elements, this concept offers a more coherent explanation of how individuals are economically resilient. In addition, this study maps new directions for future research and provides a geographic analysis of the literature. This study provides a concept of economic resilience that can be adopted to support sustainable welfare and offers practical implications for developing an index of economic resilience.